Polydimethylsiloxane (PDMS) Membrane for Separation of Soluble Toluene by Pervaporation Process - Salam H. Rasheed; Salah S. Ibrahim; Qusay F. Alsalhy; Hasan Sh. Majdi (Membranes, 2023)
A commercial polydimethylsiloxane (PDMS) membrane was employed to separate the soluble toluene compounds (C7H8) from an aqueous solution via the pervaporation (PV) process. The performance and the efficacy of the PDMS PV membrane were evaluated through the estimation of the permeation flux and separation factor under various operating parameters. The response surface method (RSM) built in the Minitab-18 software was used for the design of the experiment in this study, and the responses of the permeation flux and the separation factor were analyzed and optimized based on the operating conditions. A nonlinear regression analysis was applied to the experimental output and input, and as a result, a quadratic equation model with parameters interactions was obtained as mathematical expressions to predict the permeation flux and separation factor. At the optimal conditions of temperature 30 °C, initial toluene concentration 500 ppm, and feed flowrate 3.5 L/min, the toluene permeation flux and separation factor were 125.855 g/m2·h and 1080, respectively. The feed concentration was the most impactful and significant in the improvement of the permeation flux and separation factor of the PDMS membrane.